Técnicas para fomentar la lectoescritura en los estudiantes con necesidades educativas específicas de la Educación General Básica - Gómez Lema, Galo Alexis (2023)
Reading and writing is a fundamental skill in the formation of individuals capable of understanding, communicating and participating fully in society. Currently, education faces the challenge of adapting to a constantly evolving technological environment and addressing the diverse needs of students, including those with specific learning difficulties. This research project aims to address a comprehensive set of issues related to literacy in the context of inclusive education. Starting from the premise that each student is unique and may have different learning styles, pedagogical and technological strategies will be explored that allow adapted and effective teaching. In addition, special attention will be paid to specific learning difficulties, such as dyslexia and dysgraphia, which often go unnoticed and require differentiated approaches. Likewise, specific pedagogical strategies will be delved into, such as the Orton-Gillingham method, which has proven to be highly effective in addressing literacy difficulties. Teacher training in inclusive approaches will be promoted and the importance of early intervention in the identification and support of students with difficulties will be highlighted.